Little Indiana : small town destinations - Nunemaker, Jessica (Quarry Book, an imprint of Indiana University Press, 2016)
Where was James Dean's hometown? What do A.J. Foyt, Mario Andretti, and Al Unser have in common besides winning the Indianapolis 500? Where was the world's first theme park? Find these answers and more in Little Indiana: Small Town Destinations. Featuring towns of 15,000 or fewer inhabitants, Little Indiana explores where to eat, stay, play, and shop in over 90 small towns. After six years of traveling the state in search of amazing local experiences, blogger and TV host Jessica Nunemaker shares a treasure trove of what to expect in Hoosier small towns. Perfect for any length of excursion-day or weekend-the book is organized by region and town and provides travelers easy access to information found nowhere else. From wineries to antique shops, alpaca farms to chocolate stores, unique attractions are awaiting discovery. Full-color images showcase specialty stores, mouth-watering meals, and exciting attractions tucked off the beaten path. Proof that there's always something to do in a small town, this book is the perfect way to kick-start your next Indiana adventure!